1998
DOI: 10.2307/3870647
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Parameters of the Shoot Apical Meristem in Arabidopsis

Abstract: The shoot apical meristem (SAM) is a small group of dividing cells that generate all of the aerial parts of the plant. With the goal of providing a framework for the analysis of Arabidopsis meristems at the cellular level, we performed a detailed morphometric study of actively growing inflorescence apices of the Landsberg erecta and Wassilewskija ecotypes. For this purpose, cell size, spatial distribution of mitotic cells, and the mitotic index were determined in a series of optical sections made with a confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 0 publications
1
72
0
3
Order By: Relevance
“…Approximately 50 cell generations are required per mouse generation (61,62). Establishing the corresponding number for Arabidopsis is problematic because mitotic activity primarily is concentrated in a few meristematic zones, and cell division rates vary widely within a single meristem (63). Whatever the cause, the slow rate of telomeric DNA loss in conjunction with the global qualitative changes that occur in telomeres of telomerase-null mutants indicate that Arabidopsis will be a useful model for investigating telomere maintenance mechanisms in higher eukaryotes.…”
Section: Figmentioning
confidence: 99%
“…Approximately 50 cell generations are required per mouse generation (61,62). Establishing the corresponding number for Arabidopsis is problematic because mitotic activity primarily is concentrated in a few meristematic zones, and cell division rates vary widely within a single meristem (63). Whatever the cause, the slow rate of telomeric DNA loss in conjunction with the global qualitative changes that occur in telomeres of telomerase-null mutants indicate that Arabidopsis will be a useful model for investigating telomere maintenance mechanisms in higher eukaryotes.…”
Section: Figmentioning
confidence: 99%
“…Spatial analysis of cell division patterns in meristems has revealed that stem cells, the ultimate source of all shoot and root cells, proliferate very slowly. Their immediate progeny, which form the flanks of the shoot meristem from which lateral organ primordia arise, or the initials in the root that generate the cell types of the root, proliferate slightly faster (3)(4)(5). Subsequently, in newly initiated leaf primordia and in the domain distal to the initials in the root, a rapid increase of cell division rates is observed (5-7).…”
mentioning
confidence: 97%
“…Thus, numerous studies report the occurrence of nonanticlinal divisions in the tunica layers as indicative of the site of presumptive leaf formation (3). This altered pattern of cell division may also be accompanied by an increase in cell proliferation (4). However, whether the observed changes in cell division pattern are causally involved in leaf initiation remains debatable.…”
mentioning
confidence: 99%